Cruising QE 2 to the Orient [videorecording (DVD)] - Jones, Doug, 1948- (Distributed by Questar, Inc., 2007)
An incomparable cruise experience awaits aboard the legendary Queen Elizabeth 2, the last ship of her kind on earth. Your once-in-a-lifetime itinerary includes some of the most beautiful and fascinating travel destinations in the world: Sydney, Brunei, Beijing, and Bangkok.